Alkali pug bake process for the decomposition of monazite concentrates. (1st August 2017) - Berry, L.; Galvin, J.; Agarwal, V.; Safarzadeh, M.S.
Graphical abstract: Highlights: Alkali pug bake decomposition of monazite. Partition of heavy and light rare earth elements. Study of reaction kinetics. Opportunities for selective leaching. Abstract: An alkali pug bake-leach process was studied for the decomposition of monazite and extraction of rare earth elements (REEs), uranium, and thorium. Under the conditions studied, 4 h bake time and 210 °C with an alkali to concentrate ratio (A/C) of 4:1 allowed for relatively high REEs extraction while maintaining relatively low thorium and uranium extraction, which may allow for at least partial separation of REEs from thorium and uranium. At this level, and with an average particle size of 81 µm, more than 90% of REEs were extracted, uranium extraction dropped to ∼38% by partly reporting to the water leach solution, and thorium extraction was consistently low at ∼25%. Baking temperature (180–250 °C) was found to have a pronounced effect on the extraction of REEs, uranium, and thorium. The maximum extraction of REEs was achieved during the 210 °C, 3 h bake time test. Thorium extraction was greater than 90% in the 2 h bake time at 210 °C, then dropped drastically to 50% or less for the 3 and 4 h bake times. Uranium extraction preferred the 250 °C level, but remained fairly low for the vast majority of the levels tested. The effect of particle size (48–137 μm) was studied at 210 °C and was found to have some effect on the extraction in the 1 and 2 h tests. However, in the 3 and 4 h tests, extractions were of similar magnitude for all three particle sizes studied. Thorium extraction peaked during the 2 h test and then dropped in 3 and 4 h tests. Alkali consumption was calculated and found to increase with increasing temperature and decreasing particle size (0.01–0.22 g alkali/g concentrate). Alkali consumption was increased with increasing extraction. The drop off in extraction is attributed to the dehydration of the hydroxides produced and the formation of insoluble phosphate phases.